Using Technology in Home-School Partnerships During Covid-19 - Murni Sianturi; Markus Palobo (Musamus Journal of Mathematics Education, 2023)
Parental engagement in guiding children to study at home and the use of technology in home-school partnerships are necessary during the Covid-19 pandemic. Our case study described the experience of a career mother who lived away from her family in collaborating with her child’s school, and how technology can be used in that collaboration. We found that technology offered benefits to her, such as intensive distance communication with her child, reviewing her child’s learning remotely, and allowing communication with her child’s school. However, challenges such as the school’s attitude in supporting parental engagement, the lack of openness of the school to receive input from parents, and school unpreparedness to adapt to technology were visible. Yanti attempted to overcome the challenges by intensely asking teachers and the child and initiating to build a group of parents. Although she also employed a private tutor to keep her child on track, this approach might weaken parent-school collaboration as the parents did not rely too much on school anymore. Therefore, to establish strong home-school partnerships, the school might adjust the school culture by providing complete student learning updates, welcoming any parents’ input, and adapting to the digital era by optimizing technology.